An optimized extended kalman filter for speed sensorless direct troque control of an induction motor - Alsofyani, I. M. (2012)
This paper presents a new approach of optimizing the performance of an Extended Kalman Filter (EKF) using particle swarm optimization (PSO) for speed estimation of an induction motor drive. The development of the EKF algorithm and selection of the filter covariance for the EKF based speed estimation are presented and discussed. The effectiveness of the optimization technique is verified through Matlab/Simulink simulation of a direct torque control (DTC) drive system under various operating conditions.